Surgical techniques: Stereoelectroencephalography-guided radiofrequency-thermocoagulation (SEEG-guided RF-TC). (April 2020) - Bourdillon, Pierre; Rheims, Sylvain; Catenoix, Hélène; Montavont, Alexandra; Ostrowsky-Coste, Karine; Isnard, Jean; Guénot, Marc
Highlights: The pooled seizure-free and responder rates after SEEG-guided RF-TC are 23% and 58%, respectively. The risk of complications is low: 2.5% of patients suffer from permanent neurological deficit. The best results are obtained for periventricular nodular heterotopia (38% seizure-free and 81% responders). Concerning TLE, SEEG-guided RF-TC is inferior to anterior temporal lobectomy. Abstract: Stereoelectroencephalography-guided radiofrequency-thermocoagulation (SEEG-guided RF-TC) consists of coupling SEEG investigation with RF-TC stereotactic lesioning directly through the recording electrodes. In this systematic review the surgical technique, indications, and outcomes are described. Maximum accuracy is reached when a frame-based procedure with a robotic assistance and a per-operative vascular X-ray imaging are performed. Monitoring of the lesioning procedure based on the impedance, a sharp modification of which indicates that the thermocoagulation has reached its maximum volume, allows the optimization of the lesion size. The first indication concerns patients in whom a SEEG is required to determine whether surgery is feasible and in whom resection is indeed possible. Even if surgery is performed owing to insufficient efficacy of SEEG-guided RF-TC, the procedure remains interesting owing to its high positive predictive value for good outcome after surgery. The second indication concerns patients in whom phase I non-invasive investigations have concluded to surgical contraindication and who may still undergo SEEG in a purely therapeutic perspective (small deep zones inaccessible to surgery and network nodes of large epileptic networks). Lastly, SEEG-guided RF-TC can be considered as a first-line treatment for periventricular nodular heterotopia (PNH). Independently of indication, the overall seizure-free rate is 23% and the responder rate is 58%. The best results are obtained for PNH (38% seizure-free and 81% responders), while the worst results have been reported for temporal lobe-epilepsy in a dedicated study. The overall complication rate is 2.5%. More evidence is needed to help determine the exact place of SEEG-guided RF-TC in the surgical management algorithm.